Real-time ultrasound-guided laryngeal mask assisted percutaneous dilatational tracheostomy versus bronchoscopy-guided percutaneous dilatational tracheostomy in critically ill patients: a randomized controlled trial - Sameh Taha; Jihad Mallat; Mohamed Elsaidi; Ashraf Al-Agami; Ahmed Taha (BMC Pulmonary Medicine)
Abstract Background Percutaneous dilatational tracheostomy (PDT) is a common procedure for mechanically ventilated patients in the intensive care unit (ICU). This study compared the real-time ultrasound-guided PDT using a laryngeal mask airway (LMA) with the standard bronchoscopy-guided PDT technique in ICU patients requiring elective tracheostomy. Methods This randomized controlled study was conducted at Ain Shams University Hospital’s Critical Care Department from December 4th, 2021, to December 3rd, 2022. The study population included 60 critically ill patients admitted to the ICU. Thirty patients were randomly assigned to the real-time ultrasound-guided LMA-assisted group, and 30 patients were randomly assigned to the bronchoscopy-guided technique. The primary study outcome was the procedure time, and the secondary outcomes included procedure-related complications rate and cost-effectiveness. Results The real-time ultrasound-guided LMA-assisted group had significantly shorter procedure time (median 17 [IQR: 15–20] min vs. 35 [IQR: 28–39] min, p < 0.001) and lower equipment damage (0% vs. 20%, p = 0.024) during the procedure compared to the bronchoscopy-guided group. Additionally, the cost of tracheostomy was significantly lower in the real-time ultrasound-guided LMA-assisted group (median: 300 vs. 800 USD, p < 0.001). The real-time ultrasound-guided LMA group had a lower major complications rate than the bronchoscopy-guided group (36.7%) vs. 3.3%, p = 0.002). Conclusions The study demonstrated that real-time ultrasound-guided LMA-assisted PDT had shorter procedure time, reduced equipment damage, lower costs, and was associated with lower complications when compared to the bronchoscopy-guided technique. These findings suggest that ultrasound guidance can enhance the efficiency and cost-effectiveness of PDT procedures.